Assessing The National Zakat Amil Institution’s Financial Performance Before and During The COVID-19 Pandemic - Durohman, Hapid; Marwa, Siti Shofia; Andini, Friska Aulia Dewi (Islamic Economics and Business Review, 2023)
Abstract This research aims to examine the financial performance differences of the National Zakat Collection Institutions (LAZNAS) before and during the COVID-19 pandemic. In this study, researchers conducted a comparative analysis of LAZNAS's financial performance before and during the COVID-19 pandemic using a quantitative descriptive research approach. The data used are secondary data from the financial reports of zakat collection institutions published on their websites for four periods: pre-pandemic (2018-2019) and during the pandemic (2020- 2021). Data analysis involved assessing LAZNAS's financial performance based on activity ratios (zakat allocation ratio) and growth ratios (growth of zakat). Subsequently, non- parametric tests, specifically the Wilcoxon sign rank test using STATA 17. The research findings indicate that there is no significant difference in the performance of zakat collection institutions based on activity ratios. However, the performance of zakat collection institutions based on growth ratios shows a significant difference, as evidenced by the results of the growth of zakat calculations. This implies that there is a difference in the collection of zakat funds by LAZNAS during the COVID-19 pandemic. Keywords: Zakat ; Financial Performances ; National Amil Zakat Institution ; Covid-19.   Abstrak Penelitian ini bertujuan untuk menguji perbedaan kinerja keuangan Lembaga Amil Zakat Nasional (LAZNAS) sebelum dan selama pandemi COVID-19. Dalam penelitian ini, para peneliti melakukan analisis perbandingan kinerja keuangan LAZNAS sebelum dan selama pandemi COVID-19 menggunakan pendekatan penelitian deskriptif kuantitatif. Data yang digunakan adalah data sekunder dari laporan keuangan lembaga pengumpulan zakat yang dipublikasikan di situs web mereka selama empat periode: sebelum pandemi (2018-2019) dan selama pandemi (2020-2021). Analisis data melibatkan penilaian kinerja keuangan LAZNAS berdasarkan rasio aktivitas (rasio alokasi zakat) dan rasio pertumbuhan (pertumbuhan zakat). Selanjutnya, uji non-parametrik, khususnya uji peringkat tanda Wilcoxon menggunakan STATA 17. Temuan penelitian menunjukkan bahwa tidak ada perbedaan signifikan dalam kinerja lembaga pengumpulan zakat berdasarkan rasio aktivitas. Namun, kinerja lembaga pengumpulan zakat berdasarkan rasio pertumbuhan menunjukkan perbedaan signifikan, sebagaimana dibuktikan oleh hasil perhitungan pertumbuhan zakat. Ini mengimplikasikan bahwa terdapat perbedaan dalam pengumpulan dana zakat oleh LAZNAS selama pandemi COVID-19. Kata kunci: Zakat; Kinerja Keuangan; Lembaga Amil Zakat Nasional; Covid-19.